Advocates' Compliance and Challenges to the Implementation of e-Litigation in Divorce Cases at the Medan Religious Court Based on PERMA Number 1 of 2019 - Hasibuan, Fatta Arbie Permadi; Lubis, Fauziah (LEGAL BRIEF, 2025)
The implementation of e-Litigation regulated in Perma Number 1 of 2019 is a form of reform of the judicial system to improve efficiency, transparency, and accessibility of law in the digital era. Within this framework, the author determines the formulation of the problem to solve how compliance and obstacles and solutions in the implementation of e-Litigation in Divorce Cases at the Medan Religious Court Based on PERMA Number 1 of 2019, the purpose of this study is to Analyze advocate compliance with the implementation of e-Litigation according to PERMA Number 1 of 2019, Identify the challenges and obstacles of advocates in divorce cases through e-Litigation, Propose solutions to overcome obstacles in the implementation of e-Litigation at the Medan Religious Court. In this study, the author uses the empirical normative juridical research method. In this study, legal documents, field data, and various secondary data such as laws and regulations, court decisions, and legal theories are used. Advocates play a key role as legal assistants who are responsible for mastering electronic procedures, implementing professional ethics, and protecting client data. However, the implementation of this system faces several challenges, especially in divorce cases, such as gaps in technological infrastructure, parties’ unfamiliarity with the e-Litigation mechanism, and concerns regarding data security. This article highlights the strategic role of advocates in ensuring a fair and inclusive judicial process through e-Litigation. In addition, it is proposed to improve training, strengthen technological infrastructure, and develop supporting regulations to overcome existing obstacles. In conclusion, the success of e-Litigation is highly dependent on the synergy between technical readiness and the role of advocates in supporting technology-based access to justice